PELATIHAN PEMBUATAN PAVING BETON DARI LIMBAH PEMBAKARAN GENTENG DI DESA PEJATEN, KEDIRI KABUPATEN TABANAN - Widnyana, I Nyoman Suta; Artana, I Wayan; Laintarawan, I Putu; Indriani, Made Novia (JURNAL SEWAKA BHAKTI, 2025)
Genteng is a craft made of clay that is shaped and fired to be used as a roof covering building material. One of the craftsmen of genteng made from clay is in Bali, namely in Tabanan Regency, Kediri District, Pejaten Village. The genteng industrial center in Pejaten Village produces 10,000 pieces of genteng per day and employs around 10 workers. The problem that occurs is the waste from burning genteng which can pollute the environment and have a negative impact on the community around the industry. In this study, waste from burning genteng will be utilized as a mixture for making concrete paving. The method used is a descriptive survey method, namely by surveying, testing concrete paving and socialization. Based on the results of the implementation of community service activities that have been carried out, several things can be concluded, namely: the socialization of making concrete paving is highly appreciated and welcomed enthusiastically by roof tile/brick craftsmen in the traditional village of Pejaten, this is because it can be directly felt and utilized by the craftsmen. This socialization is also very targeted because it is given directly to the craftsmen in the village and is expected to open their insights in managing environmentally friendly waste. This can be seen from the questions asked by the craftsmen there during the socialization. There are two benefits that can be obtained from the socialization of concrete paving, namely: reducing waste from burning and providing benefits for genteng / brick craftsmen in the Pejaten traditional village.